Impact of wild boars on the feeding behavior of smaller frugivorous mammals - Osugi, Shigeru; Trentin, Bruna Elisa [UNESP]; Koike, Shinsuke (Springer Nature, 2019)
We examined the interspecific relationships among wild boars, raccoon dogs, and badgers with regard to the consumption of fallen fruits to assess how the presence of the largest mammal, the boar, affects the frugivory behavior of the two smaller species. In our 2-year survey, automatic cameras were set under the crown of wild cherry trees to observe frugivory; all mammals had access to the trees in the first year, but only wild boars were blocked access with a fence in the second year. The survey was conducted in a temperate broad-leaved forest in central Japan. All three species frequently visited those trees with abundant fruit production, and the presence of wild boars affected the feeding behavior of smaller badgers and raccoon dogs. When wild boars were present, the raccoon dogs partly shifted the time of day when they fed and tended to shift to places that the wild boars visited infrequently. In contrast, the badgers partly shifted the time of day when they fed and reduced their feeding time per visit. When wild boars were excluded from the area, raccoon dogs and badgers, which are generally nocturnal, consumed fruit under the crown not only at night but also during the day. The reason for this may be that the smaller species may not have yet responded to the sudden exclusion of the boar as a competitor. Our findings indicate that these three frugivorous mammals exhibit resource partitioning of fallen fruits on the forest floor.
Keywords: Fallen fruit; Frugivory; Melesmeles; Nyctereutesprocyonoides; Susscrofa